Characterization of carbon nanotube epoxy composites and carbon nanotubes/laminated carbon fibre epoxy composites - Mohd Tamyis, Najihah (2019)
Over the last few decades carbon fibre reinforced polymer (CFRP) was used extensively because it offers attractive mechanical and thermal properties. Aircraft and some of high-end automobile constructions used CFRP, as it has an ability to be stuctured to aerodynamic efficient configurations. However, multi –layer laminates failure behavior is complex especially woven fabric composites. CFRPs’ typical failure modes include matrix fracture, interface debonding between fibre and matrix and interlaminar delamination. One of the techniques to overcome such failure modes is by reinforcing the composites with nanoparticles. In this study, the objective is to develop a tougher resin by dispersing multiwalled carbon nanotubes (MWCNTs) into the resin which will improve the properties of CFRP composites. Two types of MWCNTs were used which lengths, a) MWCNT_long (length 10-30 μm) and b) MWCNT_short (length 0.5-2 μm).